Generative artificial intelligence in education: towards a human-centric approach - Baldassarre, Michele; Sarcina, Francesco Pio; Cuzzi, Anna Maria (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
The introduction of Generative Artificial Intelligence (GAI) technologies into the field of education is one of the most significant and debated developments in recent years. The contribution intends to provide a critical analysis of benefits and challenges related to Artificial Intelligence (AI) to guide educators, policymakers, and stakeholders in making informed decisions about JHA in the educational system. The presentation of application examples of AI educational technologies, to be used to empower teaching and learning processes, paves the way for new ways of interaction and educational support, from a perspective of inclusiveness and pedagogical innovation that always promotes a human- centred approach.